(untitled) (Applied Research and Innovation, 2023)
Stevia (Rebaudiana bertoni) leave is an ancient perennial shrub mostly found in South America (especially Brazil and Paraguay). It contains a low-calorie sweetener, which is about 300 times sweeter than sucrose. Natural sweeteners extracted from plant and artificial or synthetic sweeteners produced from industires, are the two types of sweeteners that are available. Sweetening agents induce and enhance sweet taste which makes it favorable for consumption. Natural sweetening agents are more advisable to use than artificial sweetening agents because they do not have any side effect and is of no harm to health. In this work, the background of stevia leave, uses, and extraction of natural sweetener is reviewed.